Medicines Regulation as the Handmaiden in Achieving Universal Health Coverage in Sri Lanka : the 60-year Journey - Weerasuriya, K. (Faculty of Medicine, University of Colombo, 2020)
Knowing is not enough; we must apply. Willing is not enough; we must do - Goethe Medicines Regulation is primarily for public health benefit and the pharmaceutical industry should operate under this umbrella. However, it is often diluted by considerations of the exorbitant profit and rent seeking of the industry. This presentation will discuss whether Medicines Regulation in ad hoc manner at the beginning (with Prof Bibile and Lionel the pioneers from the 1960s) and then through the Ministry of Health and now through the National Medicines Regulatory Authority has achieved "Medicines relevant to health care needs at affordable prices".
Keywords: Sri Lanka; Medicines Regulation